Early numeracy level of year 1 primary school pupils in a felda area in Negeri Sembilan - Syed Zamri, S.N.A. (2008)
Numeracy is at the forefront of contemporary educational in several parts of the world; however it is a relatively new concept in Malaysia. The focus of this research is early numeracy which refers to early mathematical competence or underlying foundations to be mastered by children before they begin learning the formal mathematics in Year 1. Despite the lack of consensus and clarity regarding the meaning of early numeracy, van de Rijt (1996) as reported by Torbeyns, et al. (2002) identified eight aspects considered crucial for developing early numeracy. Her 'synthetic model' incorporated both Pigetian perspectives and counting skills. Specifically, the eight aspects of early numeracy include concepts of comparison, classification, one-to-one correspondence, seriation, use of number words, structured counting, resultative counting and general understanding of number words.